Counter-hegemonic practices: a study of the song text of the Apoͻ festival of the Bono people of Techiman in Ghana. Issue 1 (2nd January 2022) - Nyarko-Takyi, Gertrude; Arthur, Peter; ResCue, Elvis
Abstract : This study explores the issue of counter-hegemony in traditional rule. The main focus is on how power is exhibited by traditional rulers and other people in authority, and how this power is resisted by the subjects of the ruling class. The study also examines how cultural practices such as festival songs are used as a mechanism for social control. The focus is on the Apoͻ songs of the Bono people of Techiman in Ghana. The songs are examined from the perspective of polyphony discourse by drawing on the major theories of Mikhail Bakhtin. Content analysis is adopted in exploring elements of counter-hegemony in the songs, while contextualising the elements in the broader literature. It is concluded that society has its own in-built mechanism for social control. It is realised that Apoͻ festival songs are used as a medium to keep members of the society, high or low, within socially prescribed boundaries. The songs target wrongdoers, especially the traditional authorities, and bring them to book by shaming them publicly. These songs therefore help to heal the soul of those who are wronged, and thus a natural balance in moral justice is (re)created for better social harmony. The conclusion is that the Apoͻ songs help cleanse and purify the Bono people of Techiman.